Decision support system for evaluating the elements of data transmission systems - A. A. Oleynikov; A. A. Sorokin; I. A. Beresnev (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Aim. At present, the construction of data transmission networks is undergoing rapid development, which actualized the problem of the timely maintenance, repair, and modernization of network equipment. This article provides a step-by-step description of the decision support system for evaluating the elements of data transmission systems used to improve the efficiency of telecommunication network maintenance. Method. The research methodology involved the methods of system analysis, fuzzy set theory, neural networks, graph theory, and mathematical modelling. Results. A decision support system was developed for evaluating the operational state of the elements of data transmission system during operating the network infrastructure of a communications service provider. Conclusion. The developed decision support system reduces the workload of highly qualified personnel and improves the quality of decisions made during the development of data transmission networks.